Konseptual Dan Implementasi Green Financing Perbankan Pada BANK BNI - Sufi, Anggi Primadani; Azmy, Ahmad; Febriansyah, Febriansyah (CV. ITTC INDONESIA, 2024)
In an effort to overcome climate change and support sustainable development, green financing has become an important instrument that is increasingly receiving global attention. Green financing refers to the allocation of financial resources to finance projects that aim to improve the environment, reduce carbon emissions, and encourage a sustainable economy. This type of research is literature study research with a literature review approach. This research was carried out by collecting information data based on observations. The author also uses literature to support data and information relevant to books or other sources related to green financing.